Programa escola 2030: Qual educação? Para qual projeto social? - Preuss, Joice Andrade (2022)
This research is linked to the Research Line: Society, Knowledge, and Education, of the Graduate Program in Education, at Master's level (PPGEFB), by the State University of West Paraná (UNIOESTE), Francisco Beltrão Campus, PR. The research had as its object of study the Escola 2030 Program, established in Francisco Beltrão, PR, by Municipal Law No. 4,632, of 2019. An initiative of the municipal administration that established criteria for the choice of school managers, a selection process for teachers who have already taken a public exam. , outsourced training for teachers focused on practical procedures and apostille. Our general objective was/is to understand the pedagogical, political and social foundations of the Escola 2030 Program, explaining the contradictions between the ideal and the local reality. We also seek to understand and place in the social, historical, political, methodological and conceptual context the educational reforms that were proposed at the Nossa Senhora do Sagrado Coração Municipal School. The research has a theoretical, bibliographic and documentary character, with a qualitative approach. In this sense, we carried out a survey and analysis of the documents that guided the process, we used as sources, laws, public notices, Pedagogical Political Project, articles in newspapers, minutes of the City Council, posts on the official page of the Municipality of Francisco Beltrão, as well as in the facebook page. As a theoretical-methodological perspective, we use the historical-dialectical materialism, in order to identify and analyze the contradictions, possibilities and limits of the School 2030 Program. of the program that presents meritocracy as a foundation and was implemented in a school located in a suburban neighborhood. The research revealed that the Escola 2030 Program complies with the current political and social conjuncture, in which neoliberalism is strengthened, with interventions that disqualify what is public, with the withdrawal of rights, proposals for reforms that weaken the struggle of workers, and favor the precariousness of employment contracts. However, despite the favorable scenario for the proposal, we found that the mobilization of teachers and the actions of the union, dismantled the original proposal. The research results indicated that the proposals announced by the program were not fulfilled. We believe that the results of this research contribute to the debate, reflection and understanding of current education projects.